2019
DOI: 10.18517/ijaseit.9.3.8011
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Lactic Acid Bacteria and Yeasts towards Chemical, Physical and Organoleptic Qualities of Mutton Salami

Abstract: Mutton has exceptional qualities such as smell, high consistency, and huge muscle fat, which makes mutton are restricted to consume. To expand mutton utilization, diversification with proper innovation is important. Salami is one of the proper mutton products that required starter such LAB that can deliver metabolites to change the texture, taste, and odor of meat. Other than LAB, yeasts additionally show up in meat processing, particularly in salami fermentation, which can build the meat taste and odor. The s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 16 publications
0
6
0
1
Order By: Relevance
“…Furthermore, in association with the research reported [21,22], chitosan supplementation significantly increased the rate of lipolysis, reduced the rate of adipocyte hypertrophy, triglyceride accumulation, and activity of lipoprotein in adipose tissue of the epididymis, also decreased the activity of liver enzymes [24] related to lipid biosynthesis [25]. Chitosan supplementation has been reported to activate phosphorylated adenosine monophosphate (AMP) significantly-activated protein kinase (AMPK) [26,27], and a high-fat diet induces the expression of lipogenic transcription factors (Peroxisome Proliferator-Activated Receptor Gamma/PPAR-γ and sterol receptor element-binding protein 1c/ SREBP1c) [28] in the liver and adipose tissue -29,30].…”
Section: Resultsmentioning
confidence: 82%
“…Furthermore, in association with the research reported [21,22], chitosan supplementation significantly increased the rate of lipolysis, reduced the rate of adipocyte hypertrophy, triglyceride accumulation, and activity of lipoprotein in adipose tissue of the epididymis, also decreased the activity of liver enzymes [24] related to lipid biosynthesis [25]. Chitosan supplementation has been reported to activate phosphorylated adenosine monophosphate (AMP) significantly-activated protein kinase (AMPK) [26,27], and a high-fat diet induces the expression of lipogenic transcription factors (Peroxisome Proliferator-Activated Receptor Gamma/PPAR-γ and sterol receptor element-binding protein 1c/ SREBP1c) [28] in the liver and adipose tissue -29,30].…”
Section: Resultsmentioning
confidence: 82%
“…When the protein contents of the samples were compared in relation to the storage times, no significant difference was found between the samples, except for E and F ( p > 0.05). The ability to break the protein molecules in food is limited to a few species microorganisms that can produce extracellular proteolytic enzymes (Suryaningsih et al., 2019). Due the synergistic effect between the cultures and the proteolytic enzyme activities, the protein molecules in the salami produced using the combined starter culture (F) were broken down, and the protein content was reduced compared to the control group.…”
Section: Resultsmentioning
confidence: 99%
“…Activation of cGAS-STING has also been shown to activate interferondependent type-1 protein (IIFN-defendant), then dendritic cells become active. Furthermore, it is reported that dendritic cell activation enhances the polarization response of T-helper 1 (TH1) cell protein [33][34][35][36][37]. TH1 activation increases interferon-gamma (IFM), thereby stimulating the synthesis of immunoglobulin G (IgG) to be circulated into the extracellular fluid.…”
Section: Resultsmentioning
confidence: 99%